Hedging export revenue risk using futures and options - Udo Broll; Jack E. Wahl (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1991)
This paper presents a model of a competitive risk-averse exporting firm under exchange rate risk. We show that export and hedging decisions can be separated if futures and currency options are available. A full hedge of uncertain export revenue occurs if the futures market is unbiased and the currency option premium is fair. Furthermore, institutional aspects of introducing hedging markets are presented.
Keywords: 330